ADAMTS13 exerts a thrombolytic effect in microcirculation - Crescente, Marilena; Thomas, Grace M; Demers, Melanie; Voorhees, Jaymie R; Wong, Siu Ling; Ho-Tin-Noé, Benoit; Wagner, Denisa D (Thrombosis and haemostasis, 2012)
Recombinant tissue plasminogen activator (r-tPA) is the drug of choice for thrombolysis, but it is associated with a significant risk of bleeding and is not always successful. By cleaving von Willebrand factor (VWF), the metalloprotease ADAMTS13 (a disintegrin-like and metalloprotease with thrombospondin type I repeats-13) down-regulates thrombus formation in injured vessels. We investigated whether recombinant ADAMTS13 (r-ADAMTS13) induces thrombolysis in vivo in mice. Thrombosis was produced by ferric chloride-induced (FeCl(3)) injury in the venules of a dorsal skinfold chamber. Phosphate-buffered saline (PBS, vehicle), r-tPA or r-ADAMTS13, supplemented with hirudin (to stop on-going thrombin generation), was directly applied onto the occluded vessel, and thrombus dissolution was evaluated by intravital microscopy. The incidence of blood flow restoration significantly increased 30 minutes (min) after r-ADAMTS13 vs. PBS treatment (60% vs. 0%, p<0.05) and 60 min after r-tPA treatment (75% vs. 17%, p<0.05). Both r-tPA and r-ADAMTS13 significantly reduced thrombus size 60 min after their superfusion (53.2% and 62.3% of the initial thrombus size, p<0.05 and p<0.01, respectively). Bleeding occurred in all r-tPA-treated chambers, while it was absent in mice treated with r-ADAMTS13 or PBS. We observed that, similar to r-tPA, r-ADAMTS13 can dissolve occlusive thrombi induced by FeCl(3) injury in venules. In contrast to r-tPA, the in vivo thrombolytic effect of ADAMTS13 was not associated with any signs of haemorrhage. ADAMTS13 could represent a new therapeutic option for thrombolysis.